2017
DOI: 10.1002/oa.2630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Hydroxide Treatment and Ultrafiltration on the Removal of Humic Contaminants from Archaeological Bone

Abstract: This study compared bone collagen extraction techniques that included treatment with sodium hydroxide and 30 kDa ultrafilters using a set of well-preserved, humic-contaminated archaeological marine mammal bones. Treatment with sodium hydroxide was effective at removing humic contaminants from archaeological bone, although yields were significantly decreased. Yields were also significantly decreased by ultrafiltration although this study produced no evidence that 30 kDa ultrafilters were effective at selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 29 publications
2
34
2
Order By: Relevance
“…While recent experimental research has confirmed that ultrafiltration does not have a meaningful impact on removal of a number of key contaminants (e.g. lipids, Guiry, Szpak, et al, 2016; humic acids, Szpak, Krippner, & Richards, 2017), there has been little research investigating the effects of ultrafiltration on the removal of NCPs from collagen extracts (although see Wadsworth & Buckley, 2018). However, as shown in Table 4, nearly all major NCPs present in bone, including osteonectin (32 kDa; Termine et al., 1981) osteopotinin (44 kDa; Rangaswami, Bulbule, & Kundu, 2006) and bone sialoprotein (33–34 kDa; Ganss et al., 1999) are too large for removal through ultrafiltration (even at the 30 kDa MWCO).…”
Section: Discussionmentioning
confidence: 99%
“…While recent experimental research has confirmed that ultrafiltration does not have a meaningful impact on removal of a number of key contaminants (e.g. lipids, Guiry, Szpak, et al, 2016; humic acids, Szpak, Krippner, & Richards, 2017), there has been little research investigating the effects of ultrafiltration on the removal of NCPs from collagen extracts (although see Wadsworth & Buckley, 2018). However, as shown in Table 4, nearly all major NCPs present in bone, including osteonectin (32 kDa; Termine et al., 1981) osteopotinin (44 kDa; Rangaswami, Bulbule, & Kundu, 2006) and bone sialoprotein (33–34 kDa; Ganss et al., 1999) are too large for removal through ultrafiltration (even at the 30 kDa MWCO).…”
Section: Discussionmentioning
confidence: 99%
“…Demineralized samples were then neutralized in type I water. To remove base-soluble contaminants resulting from diagenetic processes in the archaeological burial environment, samples were subjected to a series of 0.1 M sodium hydroxide (NaOH) treatments in an ultrasonic bath (NaOH solution refreshed every 15 min) until solution remained clear [ 28 ]. Collagen was then solubilized in a pH3 solution (pH adjusted with HCl) for 48 h at 65°C.…”
Section: Context Materials Methodsmentioning
confidence: 99%
“…Collagen from bones and teeth is typically the only protein that is abundantly available for archaeological analyses and, for this reason, its compositional and diagenetic properties have received considerable attention (DeNiro, 1985;Brown et al, 1988;Szpak, 2011;Guiry et al, 2016c;Szpak et al, 2017). Considering the unique growth properties of bone collagen, it may seem unreasonable that some of the following sections focus discussion on factors that cause isotopic shifts in freshwater resources on a sub annual or seasonal basis.…”
Section: Differences Between Bone Collagen and Other Tissuesmentioning
confidence: 99%